2022
DOI: 10.3390/vaccines10101608
|View full text |Cite
|
Sign up to set email alerts
|

Association between Adverse Reactions and Humoral Immune Response No Longer Detectable after BNT162b2 Booster Vaccination

Abstract: In a previous study, we described a highly significant association between reactogenicity and SARS-CoV-2 RBD IgG titers and wild-type neutralization capacity in males after basic vaccination with BNT162b2. The objective of this study was to assess whether this benefit was long lasting and also evident after BNT162b2 booster vaccination. Reactogenicity was classified into three groups: no or minor injection site symptoms, moderate (not further classified) and severe adverse reactions (defined as any symptom(s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This is the first study to examine the association between reactogenicity and pre-booster and 28-day antibody levels in a large cohort. Two previous smaller studies found no association between symptoms and antibody levels after booster vaccination with BNT162b2 [ 6 ]. In contrast, we observed a weak but statistically significant correlation between the severity of systemic symptoms and 28-day antibody levels.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This is the first study to examine the association between reactogenicity and pre-booster and 28-day antibody levels in a large cohort. Two previous smaller studies found no association between symptoms and antibody levels after booster vaccination with BNT162b2 [ 6 ]. In contrast, we observed a weak but statistically significant correlation between the severity of systemic symptoms and 28-day antibody levels.…”
Section: Discussionmentioning
confidence: 95%
“…However, in many parts of the world, primary immunizations are largely complete, and recent developments suggest that COVID-19 vaccines, similar to influenza vaccines, will require seasonal or periodic boosters. To date, only two studies have examined the interplay between reactogenicity and immunogenicity after COVID-19 booster vaccination [ 6 , 7 ]. These studies had small sample sizes (47 and 62, respectively), which limited the strengths of their findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that this pattern of reactivity reflects a pre-existing immunity induced by prior exposures to the related non-SARS hCoVs. However, it is unclear whether this T cell response will prove durable over many months: In one study of SOT recipients, no immune response was detectable after booster ( 24 ). Many SOT patients did not demonstrate robust production of antibodies was not produced until after third dose of mRNA vaccine ( 25 27 ), and antibody titers have been shown to wane after three months following a third dose ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, positive anal swabs correlate with disease severity and can serve as an early warning sign for severe illnesses. By using suitable swabbing approaches for different patients, sample collectors can obtain optimal specimens for COVID-19 testing [9,10]. Pooled sampling and pooled testing are two approaches for mass nucleic acid testing that may improve efficiency to some extent.…”
Section: Similarities and Differences Between Nucleic Acid Sampling A...mentioning
confidence: 99%